Implementasi strategi dan dampak nike sebagai brand olahraga dalam industri fashion halal - Maulidah, Dhini Citra (Nur Science Institute, 2023)
The development of halal industry trends has attracted the attention of multinational companies such as Nike to enter the halal fashion market with the launch of hijab products in 2018. This research aims to analyze the strategy implementation and impact of Nike as a sports brand in the halal fashion industry. By using descriptive qualitative methods and collecting secondary data from various sources, this research explores the reasons behind Nike's controversial move to enter this market. The results show that the launch of the Nike Pro hijab is part of the company's efforts to expand market share and improve its brand image among Muslim consumers. Additionally, this research highlights the impact of capitalism in companies' expansion strategies in this rapidly growing market, as well as the social and economic implications associated with the presence of large companies such as Nike in the halal fashion industry.